On Analytic and Subharmonic Functions in Unit Disc Growing Near a Part of the Boundary - Favorov, S.Yu.; Radchenko, L.D. (Журнал математической физики, анализа, геометрии, 2013)
In the paper there was found an analog of the Blaschke condition for analytic and subharmonic functions in the unit disc, which grow at most as a given function j near some subset of the boundary. Найден аналог условия Бляшке для аналитических и субгармонических функций в единичном круге, которые растут не быстрее заданной функции j вблизи некоторого подмножества границы.